Endotoxin-Induced Intravascular Coagulation in Rabbits:Effect of Tissue Plasminogen Activator vs Urokinase on PAI Generation, Fibrin Deposits and Mortality - Paloma, M J; Páramo, J A; Rocha, E (Thrombosis and Haemostasis, 1995)
We have evaluated the effect of plasminogen activators (t-PA and urokinase) on an experimental model of disseminated intravascular coagulation (DIC) in rabbits by injection of 20 μg/kg/h of E. coli lipopolysaccharide during 6 h t-PA (0.2 mg/kg and 0.7 mg/kg), urokinase (3000 U/kg/h) and saline (control) were given simultaneously with endotoxin. Results indicated that urokinase and low dose of t-PA significantly reduced the increase of plasminogen activator inhibitor (PAI) activity observed 2 h after endotoxin (p <0.001). High t-PA dose also diminished the PAI levels at 6 h (p <0.0001). A significant reduction of fibrin deposits in kidneys was observed in both t-PA treated groups as compared with findings in the group of rabbits infused with saline solution (p <0.005), whereas urokinase had no significant effect on the extent of fibrin deposition. Finally, the mortality rate in the control group (70%) was reduced to 50% in rabbits receiving high doses of t-PA. In conclusion, treatment with t-PA resulted in reduced PAI generation, fibrin deposits and mortality in endotoxin-treated rabbits